صناعة الطاغية في رواية "مواسم الإسطرلاب" لـ"علي لفتة سعيد - حمزاوي ريحانة (My University, 2024)
Abstract: At the heart of contemporary Arabic novels, they are found to reflect and analyze many social and political concepts and phenomena, including the theme of "the fabrication of the tyrant". This subject reveals how the personality of the tyrant is crafted in the context of the novel, and how its characteristics are built and their impact on the surrounding society. This subject delves into the depth of power and tyranny and how they impact individuals and communities. This study sheds light on how the tyrant's personality is shaped as a symbol of oppression, injustice, and persecution in the novel, as well as highlighting the psychological, social, and political aspects that play a crucial role in shaping the personality of the tyrant and their behavior. --------------- الملخص: في قلب الرواية العربية المعاصرة، نجدها تعكس وتحلل العديد من المفاهيم والظواهر الاجتماعية والسياسية، من بينها موضوع "صناعة الطاغية " فهذا الموضوع يكشف كيف تُصاغ وتُصنع شخصية الطاغية في سياق الرواية، وكيف يتم بناء سماتها وتأثيرها على المجتمع المحيط بها، فهذا الموضوع يتناول عمق السلطة والاستبداد وكيفية تأثيرها على الأفراد والمجتمعات. تسلط هذه الدراسة الضوء على كيفية تشكيل شخصية الطاغية كرمز للقمر والظلم والاضطهاد في الرواية، كما تبرز هذه الدراسة الجوانب النفسية والاجتماعية والسياسية التي تلعب دوراً حاسما في تشكيل شخصية الطاغية وسلوكه. ----------------- Résumé : Au cœur du roman arabe contemporain, on le trouve refléter et analyser de nombreux concepts et phénomènes sociaux et politiques, dont le thème de "la fabrication du tyran". Ce sujet révèle comment la personnalité du tyran est façonnée dans le contexte du roman, et comment ses caractéristiques sont construites et leur impact sur la société qui l'entoure. Ce sujet aborde la profondeur du pouvoir et de l'oppression et comment ils influent sur les individus et les communautés. Cette étude met en lumière comment la personnalité du tyran est façonnée comme un symbole de l'oppression, de l'injustice et de la persécution dans le roman, et comment elle souligne les aspects psychologiques, sociaux et politiques qui jouent un rôle crucial dans la formation de la personnalité du tyran et de son comportement.
Keywords: the tyrant; tyranny; injustice; persecution; power; repression.; الطاغية، الاستبداد، الظلم، الاضطهاد، السلطة، القمع.; le tyran; l'oppression; l'injustice; la persécution; le pouvoir; la répression